Status Epilepticus Following Labor in a Remote Area: A Case Report of Puerperal Sepsis - Silalahi, Andre Martua; Johansyah, Theodorus Kevin Putra; Gusti, Agustinus; Siswantoro, Cahyo Wicaksono (JURNAL KESEHATAN REPRODUKSI, 2023)
Background: Puerperal sepsis is one of the five leading causes of maternal mortality worldwide, commonly occurs in low to middle income countries. Higher incidence is observed in rural areas where diagnostic and therapeutic interventions may be limited.Case: A a 21-year-old woman who developed a fever, abdominal pain, and foul-smelling vaginal discharge five days after giving birth. The patient convulsed five times in total before being admitted. She was diagnosed with status epilepticus caused by sepsis-associated encephalopathy and puerperal sepsis, which was successfully treated with antibiotics and supportive care.Discussion: Pregnancy and the puerperium period involve significant changes in maternal physiology and immune function. The Society of Obstetric Medicine Australia and New Zealand (SOMANZ) has proposed Obstetric-modified quick sepsis related organ failure assessment (omqSOFA) for early recognition of maternal sepsis. An score of 2 or higher has predictive value for maternal sepsis.Conclusion: Early recognition, appropriate treatment, and close monitoring are crucial for improving outcomes in patients with puerperal sepsis.